Johann Christoph Gottscheds Briefwechsel - Historisch-kritische Ausgabe Band 3: 1734-1735 - Gottsched, Johann Christoph (Briefwechsel, 2009)
This third volume of the letter edition documents the correspondence of the years 1734 and 1735. With his appointment as professor of logic and metaphysics and his marriage to Luise Adelgunde Victorie Kulmus, Gottsched was firmly established in Leipzig by the mid-1730s. The letters offer important insights into the development of the German Society he led (especially to the first periodical on literary studies it published), into the reception and impact of his works, including his plays, and into his translating activities.